2017
DOI: 10.18632/oncotarget.18888
|View full text |Cite
|
Sign up to set email alerts
|

Plasma 25-hydroxyvitamin D levels, vitamin D intake, and pancreatic cancer risk or mortality: a meta-analysis

Abstract: BackgroundThe associations between vitamin D status, including plasma 25-hydroxyvitamin D [25(OH)D] levels and vitamin D intake, and pancreatic cancer risk and mortality are inconsistent. The aims of this study are to evaluate the antitumor and therapeutic effects of vitamin D status for pancreatic cancer patients.MethodsA literature search for relevant studies was conducted using PubMed and Embase databases. Risk ratio (RR), hazard ratio (HR), and 95% confidence interval (CI) were used as the effect measures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 76 publications
1
36
0
Order By: Relevance
“…Finland may have contributed to the findings of direct correlations between 25(OH)D concentration and incidence of pancreatic cancer. For more discussion of pancreatic cancer (51,90).…”
Section: The Cohort Consortium Vitamin D Pooling Project Of Rarer Canmentioning
confidence: 99%
“…Finland may have contributed to the findings of direct correlations between 25(OH)D concentration and incidence of pancreatic cancer. For more discussion of pancreatic cancer (51,90).…”
Section: The Cohort Consortium Vitamin D Pooling Project Of Rarer Canmentioning
confidence: 99%
“…4 A meta-analysis of 5 prospective studies found no effect of 25(OH)D concentration on pancreatic cancer incidence. 5 However, a meta-analysis of 5 cohort studies found that high vs low 25(OH)D concentration was associated with a 19% reduction in pancreatic cancer mortality rate. 5 An article reviewing racial disparities in cancer mortality rates found that for many types of cancer, blacks had much higher cancer-specific and overall mortality rates than whites did.…”
Section: Vitamin D Status May Help Explain Racial Disparities In Pancmentioning
confidence: 99%
“…There is some evidence, while not consistent, that vitamin D supplementation may increase the risk of prostate cancer; (11,15) therefore, a sensitivity analysis in the entire cohort will be done where the primary outcome will be defined as all cancers but will exclude prostate cancer. Similarly, inconsistent associations have been found between vitamin D and risk of pancreatic cancer; (18,19) and so a sensitivity analysis will be conducted after excluding cases of pancreatic cancer.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Evidence on biological plausibility from mechanistic studies and data from observational studies suggest that vitamin D status may be linked to risk of several types of cancer. (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) However, whether vitamin D supplementation lowers risk of cancer is unknown. Vitamin D is an appealing approach for prevention of cancer because of its ease of administration and low cost.…”
Section: Introductionmentioning
confidence: 99%